Implementing strategic resilience through cooperation projects with start-ups: A~multiple case study - Ann-Kathrin Dieterle; Stephanie Duchek (Schmalenbach Journal of Business Research (SBUR), 2023)
Strategic resilience is the capacity of organizations to proactively transform and renew through innovation to minimize the effects of unknown future crises. In this context, we know that cooperation plays an essential role as an external innovation strategy, and cooperation projects with start-ups related to innovation are one specific way to implement strategic change. However, research does not provide deeper insights into the process, outcomes, and success conditions of such projects. To help fill this research gap, we use the cases of two established firms using cooperation projects with start-ups related to innovation to enhance their strategic resilience. Based on an in-depth empirical investigation, we developed a framework that describes the specifics of those cooperation projects along their course (i.e., before cooperation, entry-phase into cooperation, during cooperation, and after cooperation) and resulting direct and indirect resilience benefits for the established firms. Thereby, the relationship quality (i.e., balance between formal and informal procedures, improvisation mindset, and appreciation and prioritization) turned out to be a central condition for resilience to emerge from those projects. Our framework illustrates how strategic resilience can arise from cooperation projects with start-ups related to innovation and which factors are particularly important in this context. It thus can be used as a guideline for the successful implementation of strategic resilience in practice as well as a basis for future research on the role of cooperation in strategic resilience.
Keywords: M13; M14; O31; O36; 650; Cooperation projects; Innovation; Start-ups; Strategic resilience; Strategy implementation; Transformation